Optical properties of the TeO2-PbO-Li2O-Nd2O3 glass system - Sahar, M. R.; Kassim, Azman; Rohani, M. S.; Ariffin, R. (2008)
Nd-doped Tellurite glasses of the (80-x)TeO2-10PbO-10Li2O-xNd2O3 system, where x = 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 mol% have successfully been synthesized by melt-quenching techniques. Their absorption spectra had been characterized in the ranges of 400-900 nm while the luminescence spectra are measured in the range of 400 to 1500 nm. The experimental, and calculated, oscillator strength results are found to vary from 1.1566 x 10-6 to 0.8041 x 10-6 and from 1.0257 x 10-6 to 0.7715 x 10-6 with respect to the Nd3+content respectively. Meanwhile, the Judd-Ofelt parameters, varies from 3.472 x 1020cm2 to 2.576 x 1020cm2, varies from 2.110 x 1020cm2 to 2.108 x 1020cm2 and varies from 2.424 x 1020cm2 to 2.392 x 1020cm2 with respect to Nd3+ content. From the luminescence spectra it is observed that the emission occurs at 485nm, 560nm, 605nm, 880nm, 1062nm and 1340nm, which is due to 4G9/2 → 4I9/2, 2G9/2 → 4I11/2 , 2H11/2 → 4I9/2 , 4F3/2 → 4I9/2 , 4F3/2 → 4I11/2 and 4F3/2 → 4I13/2 transitions respectively.